Saving Souls and ‘Trees’: An Emerging Model of Pentecostal-Charismatic Eco-Missions in the Church of Pentecost, Ghana - Tsekpoe, Christian (Religions, 2025)
The emergence of Pentecostal-Charismatic Christianity in Ghana has historically been characterized by a perceived schism between faith and science. This schism was particularly evident in some Ghanaian Pentecostal-Charismatic Churches (PCCs), where the use of both orthodox and herbal medications was prohibited. The rift between the two domains within the African Pentecostal-Charismatic tradition, which persisted until recent times, highlights significant implications for the intersection of religious beliefs and scientific practises within various African contexts. This traditional one-dimensional approach adopted by PCCs in Africa influenced their interpretation of the Great Commission and has resulted in the oversight of important aspects of their mission, particularly the lack of attention to the well-being of the natural environment and other non-human entities. However, there is a noticeable shift in this narrative in Ghana, as shown in the case of the Church of Pentecost, which is increasingly becoming involved in initiatives aimed at preserving the earth and its inhabitants. This article utilizes document reviews, a survey, and personal observations to examine the extent to which this emerging eco-mission is embraced within the Church of Pentecost and explores its potential as a model for PCCs in Ghana and beyond. The article proposes strategies for reimagining traditional doctrines to enable the full integration of eco-missions within the broader mission of the church.